Effectiveness and safety of Hwangryunhaedok-Tang (Huang-Lian-Jie-Du-Tang, Oren-Gedoku-to) for dyslipidemia: A protocol for a PRISMA-compliant systematic review and meta-analysis. Issue 51 (18th December 2020) - Lee, Boram; Kwon, Chan-Young
Abstract: Background: Recent experimental and clinical studies have suggested that Hwangryunhaedok-tang (HHT), an herbal formula, could improve the lipid profiles in patients with dyslipidemia. This systematic review aimed to evaluate the effectiveness and safety of HHT monotherapy or adjunctive HHT therapy with conventional lipid-lowering drugs in managing dyslipidemia. Methods: Twelve English, Korean, Chinese, and Japanese databases were comprehensively searched from their inception to January 2020. Randomized controlled trials (RCTs) using HHT monotherapy or adjunctive HHT therapy for dyslipidemic patients were included. The primary outcome was the low-density lipoprotein cholesterol (LDL-C) level. Descriptive analyses of participant details, interventions, and outcomes were conducted and where appropriate data were available, a meta-analysis was performed and presented as a risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CIs). The risk of bias was assessed using the Cochrane risk of bias tool and the quality of evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results: Nine RCTs with 536 participants were included. In comparison with lipid-lowering drugs alone, HHT as an adjunctive therapy to lipid-lowering drugs or as a monotherapy showed significantly superior (MD -1.15 mmol/L, 95% CI -1.25 to -1.05) or inferior results (MD 0.23 mmol/L, 95% CI 0.09 to 0.38), respectively, for LDL-C levels. The incidence of adverse events was significantly lower when HHT was used in addition to lipid-lowering drugs, in comparison to that with lipid-lowering drugs alone. No serious adverse events were reported in the HHT group. Most included studies showed a high risk of performance bias and the quality of evidence was rated generally "low" because of the high risk of bias and inconsistency or imprecision of the meta-analysis results. Conclusion: Current evidence suggests that HHT may be beneficial for patients with dyslipidemia and may reduce the adverse events associated with lipid-lowering drugs. However, due to the high risk of bias of the included studies and low quality of evidence for the main findings, no definitive conclusion could be reached. Further rigorous, high-quality, and placebo-controlled RCTs should be conducted to assess the efficacy of HHT. Trial registration number: PROSPERO CRD42020164563 Abstract : Supplemental Digital Content is available in the text